Influence of mixing intensity on lysozyme crystallization in a meso oscillatory flow reactor - Castro, Filipa (2018)
The influence of mixing intensity on protein crystallization has been investigated for the first time in a meso oscillatory flow reactor (meso-OFR). For this, lysozyme crystallization was studied in batch at different oscillation amplitudes and frequencies. Turbidity was monitored over time to measure induction time and follow the crystallization process. Results suggest that the crystallization mechanism may be characterized by the occurrence of primary heterogeneous nucleation followed by attrition-induced secondary nucleation. Results also evidence the non-monotonic dependence of both induction time and mean crystal size on mixing intensity. Indeed, results show that the two parameters decrease with increasing mixing intensity at Reo below 189, while for further increase of Reo both remain almost constant. Based on the literature, we suggest that such behaviour may be explained by the influence of mixing intensity on protein clusters size distribution in solution. Further, induction time and mean crystal size show a stronger dependency on the oscillation amplitude compared to the oscillation frequency, in particular at the lower amplitudes. Finally, it is shown that lysozyme keeps its activity at the end of the experiments and crystal yields are quite reasonable.